Dysfunctional uterine bleeding - diagnosis. - Pacheco Romero, José (2015)
As dysfunctional uterine bleeding abnormal bleeding not associated with organic pathology, our guidance in the diagnosis is the rule out any organic cause, determine whether or not ovulation and at what level of the hypothalamus-pituitary-ovarian axis origin is alteration.